Categorical dilemmas: challenges for HIV prevention among men who have sex with men and transgender women in Vietnam. Issue 10 (2nd October 2020) - Ly, An Thanh; Wilson, Patrick A.; Parker, Caroline M.; Giang, Le M.; Hirsch, Jennifer S.; Pham, Timothy; Parker, Richard G.
Abstract: In Vietnam, HIV continues disproportionately to affect men who have sex with men and transgender women, and the increase in HIV prevalence in these populations may be related to a lack of tailoring of current prevention approaches, which often fail to address social diversity within these populations. To effectively respond to HIV in Vietnam, it is imperative to identify sub-populations within the broad category of 'men who have sex with men' (MSM), a term which in Vietnam as in many other sites frequently subsumes transgender women. In this paper, we document the different categories used to describe people who engage in same-sex sexual practices and/or non-normative gender performances drawing on data collected via in-depth interviews and focus groups with a total of 79 participants in Hanoi. We identified over 40 different categories used to describe men who have sex with men and/or transgender women. These categories could be described as behaviourally-based, identity-based, or emic, and each carried different meanings, uses (based on age and geography) and levels of stigma. The categories shine light on the complexity of identities among men who have sex with men and transgender women and have utility for future research and programming to more comprehensively address HIV in Vietnam.